XI Ogólnopolski Zjazd Pedagogiczny Przesilenie. Budujmy lepszy świat w sobie i pomiędzy nami (Szkoła - Zawód - Praca, 2022)
XI Ogólnopolski Zjazd Pedagogiczny Przesilenie. Budujmy lepszy świat w sobie i pomiędzy nami.